Monitoring total-body inflammation and damage in joints and entheses: the first follow-up study of whole-body magnetic resonance imaging in rheumatoid arthritis. (4th July 2017) - Axelsen, MB; Eshed, I; Østergaard, M; Hetland, ML; Møller, JM; Jensen, DV; Krintel, SB; Hansen, MS; Terslev, L; Klarlund, M; Poggenborg, RP; Balding, L; et al.
Abstract : Objective : To investigate changes in whole-body magnetic resonance imaging (WBMRI) inflammatory and structural lesions in most joints and entheses in patients with rheumatoid arthritis (RA) treated with adalimumab. Methods : WBMRI was obtained at weeks 0, 6, 16, and 52 in a 52 week follow-up study of 37 RA patients starting treatment with adalimumab. Readability and reliability of WBMRI were investigated for 76 peripheral joints, 23 discovertebral units, the sacroiliac joints, and 33 entheses. Changes in WBMRI joint and entheses counts were investigated. Results : The readability of peripheral and axial joints was 82–100%, being less for elbows and small joints of the feet. For entheses, 72–100% were readable, except for entheses at the anterior chest wall, elbow, knee, and plantar fascia. The intrareader agreement was high for bone marrow oedema (BMO), bone erosion (80–100%), and enthesitis (77–100%), and slightly lower for synovitis and soft tissue inflammation (50–100%). All synovitis, BMO, and soft tissue inflammation counts decreased numerically during treatment. The 26-joint synovitis WBMRI count decreased significantly during the first 16 weeks for patients with a good European League Against Rheumatism (EULAR) response (from median 6 to 4, p < 0.05), but not for patients with a moderate or no EULAR response. There were no overall changes in structural lesions. Conclusions : WBMRI allows simultaneous monitoring of most axial and peripheral joints and entheses in RA patients and can visualize a decrease in inflammatory counts during treatment. This first WBMRI follow-up study of patients with RA encourages further investigation of the usefulness of WBMRI in RA.